Meningkatkan Kinerja UMKM Melalui Pelatihan Karyawan Berbasis Digital - Dora Indah Triana; Efniar Efniar; Violeta Nirmala (Journal of Innovative and Creativity, 2026)
Digital-based employee training can improve the performance of UMKM by equipping employees with the digital skills needed to increase productivity, efficiency and innovation. This training can help UMKM improve their ability to compete in the digital market and improve the quality of service to customers. This research aims to show how digital-based training can improve the performance of Micro, Small and Medium Enterprises (UMKM). The focus of the research is the impact of training UMKM employees in adopting digital technology, such as the use of HR software, e-learning platforms and accounting applications. The results of the research here are that digital-based training is proven to increase the efficiency and productivity of UMKM, UMKM can reach a wider market through digital marketing on social media and e-commerce platforms. The use of digital technology helps manage operations and finances more efficiently and the conclusion of this training is that increasing the competitiveness of UMKM in the digital era is very dependent on the availability of qualified human resource competencies, which can be achieved through digital-based training. Thus, digital-based employee training can be an effective solution to improve UMKM performance and increase competitiveness in the digital era.